THREE SIMPLE HEURISTICS MATHEMATICAL PROOFS ON LASSO THEORY - REIS, Carlos José dos; CARVALHO, Laerte Dias de; CHAVES, Lucas Monteiro; SOUZA, Devanil Jaques de (Brazilian Journal of Biometrics, 2020)
Three relevant facts about the least absolute shrinkage and selection operator (Lasso) are studied: The estimatives follows piecewise linear curves in relation to tuning parameter, the number of nonzero selected covariates is an unbiased estimator of its degrees of freedom and when the number of covariates p is greater than the numbers of observations n at most n covariates are selected. These results are well known and described in the literature, but with no simple demonstrations. We present, based on a geometrical approach, simple and intuitive heuristics proofs for these results.